Using The Ardl Model To Estimate The Relationship - Aoulmi ,Fadila; Garici ,Yacine (University of Eloued جامعة الوادي, 2025)
This study aims to investigate the impact of the balance of payments on foreign exchange reserves in Algeria during the period from 2013 to 2023. To achieve this objective, a descriptive analytical approach was employed in the theoretical aspect of the study, while the practical aspect involved conducting a cointegrating study based on the ARDL model to understand the relationship between the variables. The study concluded that there is a long-term positive relationship between the balance of payments and foreign exchange reserves, where each unit change in the balance of payments leads to a change in foreign exchange reserves.
مقال
Keywords: Balance of payments; foreign exchange reserves; Algeria; ARDL model.